Geothermal energy and district heating in Ny-Ålesund, Svalbard - Iversen, Julianne (UiT The Arctic University of Norway, 2013)
This thesis presents the possibilities for using shallow geothermal energy for heating purposes in Ny-Ålesund. The current energy supply in Ny-Ålesund is a diesel generator, which does not comply with the Norwegian government and Ny-Ålesund Science Managers Committee’s common goal to maintain the natural environment in Ny-Ålesund. Ny-Ålesund has a potential for replacing the heat from the current diesel based energy source with geothermal energy. Geothermal energy is considered to have low impact on the environment, and is therefore a good alternative to make Ny-Ålesund renewable. Ny-Ålesund is found suitable for the use of shallow geothermal energy. Considered factors are geology, the geothermal gradient, the groundwater flow and the permafrost depth the area. A geothermal system can be included in the existing district heating system, and replace the heat produced by the diesel generator. A model containing the geological and physical properties in Ny-Ålesund is created using COMSOL Multiphysics. Simulations of a geothermal system with a 100 meter deep pipe, show that approximately 50 such systems are needed to cover Ny-Ålesund’s heating demand. The simulations also show how a geothermal system will influence the temperature distribution around the geothermal pipe, how the geothermal system influences the permafrost depth, and how the groundwater flow effects the ground temperature.